User role analysis method based on directed topological potential - Song-qing DUAN; Xing-long YU; Bin WU; Bai WANG (Tongxin xuebao)
The majority of real-world networks are directed,weighted and dynamic.Aiming at the problem of node role analysis in directed weighted network,a novel node role analysis method based on directed topological potential is pro-posed,which can divide nodes into four roles based on their behavior pattern and local influence.Then,a node role-based dynamic networks evolution analysis method is introduced,which can model the dynamics of behavioral roles represent-ing the main connectivity patterns over time and detect the significant event.The experiment results indicate that pro-posed approaches can effectively estimate the node role and detect the dynamics of network evolution.